Feasibility and diagnostic accuracy of the Patient‐Reported Outcomes Measurement Information System (PROMIS) item banks for routine surveillance of sleep and fatigue problems in ambulatory cancer care. Issue 18 (28th June 2016) - Leung, Yvonne W.; Brown, Catherine; Cosio, Andrea Perez; Dobriyal, Aditi; Malik, Noor; Pat, Vivien; Irwin, Margaret; Tomasini, Pascale; Liu, Geoffrey; Howell, Doris
Abstract : BACKGROUND: Routine screening for problematic symptoms is emerging as a best practice in cancer systems globally. The objective of this observational study was to assess the feasibility and diagnostic accuracy of Patient‐Reported Outcomes Measurement Information System (PROMIS) computerized adaptive testing (CAT) for fatigue and sleep‐disturbance items compared with legacy measures in routine ambulatory cancer care. METHODS: Patients who attended outpatient clinics at the Princess Margaret Cancer Center completed PROMIS CAT item banks and legacy measures (the Functional Assessment of Chronic Illness Therapy [FACIT]‐Fatigue scale and the Insomnia Severity Index [ISI]) using tablet computers during clinic visits. The completion rates, patient acceptability, and diagnostic accuracy of PROMIS CAT were evaluated against legacy measures using receiver operating characteristic (ROC) curve analysis. RESULTS: Participants consisted of 336 patients (mean age ± standard deviation, 57.4 ± 15.7 years; 55% females; 75% Caucasian). Over 98% of patients did not find symptom screening was burdensome, although only 65% were willing to complete the survey at every visit. PROMIS CAT scores were significantly correlated with both FACIT‐Fatigue scores ( r = −0.83) and ISI scores ( r = −0.57; p < 0.0001 for all). Areas under the curve (AUC) by ROC analysis for fatigue were 0.946 using the FACIT‐Fatigue cutoff ≤30, 0.910 for sleep disturbance, and 0.922 for sleep impairment using the ISI cutoff ≥15. The recommended T‐score cut‐off for PROMIS CAT Fatigue was 57, Sleep Disturbance was 57, and Sleep Impairment was 57. CONCLUSIONS: The current results support the feasibility and accuracy of PROMIS CAT and its potential for use in routine ambulatory cancer care. Future research will assess feedback of these data to clinicians and evaluate effects on earlier identification of and intervention for these problems. Cancer 2016 . © 2016 American Cancer Society . Cancer 2016;122:2906–2917. © 2016 American Cancer Society Abstract : The feasibility and diagnostic accuracy of the Patient‐Reported Outcomes Measurement Information System Computerized Adaptive Testing for fatigue and sleep‐disturbance items are assessed in an observational study and compared with legacy measures. The findings support the feasibility and diagnostic accuracy of the system and its potential for use in routine ambulatory cancer care.